Stable and low-threshold photon upconversion in nondegassed water by organic crystals - Murakami, Yoichi; Enomoto, Riku (Frontiers in Chemistry, 2023)
Photon upconversion (UC) is a technology that converts lower-energy photons (longer wavelength light) into higher-energy photons (shorter wavelength light), the opposite of fluorescence. Thus, UC is expected to open a vast domain of photonic applications that are not otherwise possible. Recently, UC by triplet−triplet annihilation (TTA) between organic molecules has been studied because of its applicability to low-intensity light, although the majority of such studies have focused on liquid samples in the form of organic solvent solutions. To broaden the range of applications, solid-state UC materials have been an active area of research. We recently developed air-stable, high-performance molecular UC crystals that utilize a stable solid-solution phase of bicomponent organic crystals. This article begins with a brief overview of previous challenges in developing and improving solid-state TTA–UC materials. Then, we briefly review and explain the concept as well as advantages of our molecular solid-solution UC crystals. We applied these organic crystals for the first time to a water environment. We observed blue UC emission upon photoexcitation at 542 nm (green–yellow light) and then measured the excitation intensity dependence as well as the temporal stability of the UC emission in air-saturated water. In nondegassed water, these organic crystals were stable, functioned with a low excitation threshold intensity of a few milliwatts per square centimeter, and exhibited high photo-irradiation durability at least over 40 h; indicating that the developed organic crystals are also viable for aqueous conditions. Therefore, the organic crystals presented in this report are expected to extend the domain of UC-based photonic applications in practical water systems including in vivo diagnostic, clinical, and therapeutic applications.